Restructuring and the scope of negation in Hindi-Urdu - Rajesh Bhatt; Vincent Homer (Glossa, 2020)
In Hindi-Urdu, a negation which seems to be inside an infinitival complement can have effects typical of a matrix negation, e.g., NPI licensing in the matrix. We show that this exceptional behavior of negation is only possible with restructuring infinitives. We argue that the infinitival V moves out of the restructuring infinitive and into the matrix, and that it forms a cluster with the main verb. This movement makes the negative marker appear to belong to the embedded clause, when in fact it is in the matrix, and behaves as a matrix negation (in terms of scope and other tests). We thus have a new criterion for restructuring in Hindi-Urdu, alongside Long Distance Agreement. The existence of these two criteria allows us to explore the diversity of restructuring complements in Hindi-Urdu and show that the optionality of Long Distance Agreement is not tied to the optionality of restructuring.